Concurrent circulation of avian influenza viruses H5N1 and H9N2 enhances the genetic evolution of reassortant viruses in Egyptian poultry populations - Nahed Yehia; Mahmoud Ibrahim; Rawan Muhammad Shady; Ahmed Abd Elhalem Mohamed; Dalia Said; Mohamed E. Taha; Abdelsatar Arafa; Samah Eid; Mohamed A. Shalaby; Uwe Truyen; Rea Maja Kobialka; Ahmed Abd El Wahed; et al. (PLoS ONE, 2026)
The co-circulation of the recently emerged H5N1 clade 2.3.4.4b and the endemic H9N2 avian influenza viruses (AIV) in poultry farms has led to significant economic losses and increased the likelihood of viral reassortment. Continuous and extensive surveillance with full genome sequencing is highly recommended. The objective of this study was to monitor AIV circulating in Egyptian poultry populations throughout 2024 using molecular surveillance and to detect genetic reassortment events. A total of 50 chicken flocks that exhibited respiratory symptoms from seven governorates in Egypt were tested for avian influenza H5, H9, Infectious Bronchitis virus (IBV), and Newcastle Disease Virus (NDV) using real-time RT-PCR. Four flocks that tested positive for H5 (AN1, AN6, AN7, and AN8) and three flocks that tested positive for H9N2 (AN2, AN3, and AN4) were selected for isolation and full-genome sequencing. They were subjected to virus isolation in specific-pathogen-free (SPF) embryonated chicken eggs, and identification was done using real-time RT-PCR assay. The full-genome sequencing was performed using rapid barcoding from Oxford Nanopore Technologies. The genome analysis revealed a H5N2 reassortant virus, comprising the HA, PB2, PB1, and PA gene segments from H5N1 clade 2.3.4.4b (EA-2021-AB), while the NA, NP, NS, and M genes were from H9N2 (G5.6). Additionally, two reassorted H9N2 viruses were identified, containing HA, NA, NP, M, and NS genes from H9N2 (G5.6), and PB1, PB2, and PA genes from Highly Pathogenic Avian Influenza H5N1 virus Clade 2.3.4.4b (EA-2021-AB). Interestingly, both reassortant H9N2 viruses have specific adaptive mutations in some of their internal genes that were not present in any other Egyptian H9N2 viruses. Several mutations, potentially associated with increased virulence and mammalian adaptation, were also detected in the internal genes. This study highlights the emergence of novel reassortant AIV viruses and underscores the need for continuous molecular surveillance, as well as further studies on the pathogenicity and vaccine efficacy against these newly emerged viruses.